Employee discipline in the city of banjarmasin: case study of employee discipline in public service review at the north banjarmasin district office - Dewi Merdayanty; Arif Darmawan; Syahrial Shaddiq; Junaidy Junaidy; Sitna Hajar Malawat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Employee discipline is very important in ensuring that the public services provided run efficiently and effectively. Employee discipline is not only important for the internal operational effectiveness of an organization but also has a significant impact on the quality of public services provided to the community, especially public services in North Banjarmasin District, Banjarmasin City. The purpose of this study was to determine employee discipline in improving public services in North Banjarmasin District, Banjarmasin City. The research method uses a qualitative descriptive with a case study approach. Data collection techniques through observation, interviews, and documentation. The results of the study find (1) The discipline indicator for working time for civil servants is following the stipulated provisions, namely 37.5 hours in one week starting from Monday to Friday. (2) Disciplinary indicators for civil servant regulations are carried out under applicable procedures and all employees wear uniforms and attributes that have been determined. (3) Disciplinary indicators of civil servant work responsibilities in the use of tools and maintenance of equipment have been carried out properly, if damage occurs to the equipment, repairs are immediately carried out under established procedures